A promising natural product, pristimerin, results in cytotoxicity against breast cancer stem cells in vitro and xenografts in vivo through apoptosis and an incomplete autopaghy in breast cancer. (March 2018) - Cevatemre, Buse; Erkısa, Merve; Aztopal, Nazlihan; Karakas, Didem; Alper, Pınar; Tsimplouli, Chrisiida; Sereti, Evangelia; Dimas, Konstantinos; Armutak, Elif I. Ikitimur; Gurevin, Ebru Gurel; Uvez, Ayca; Mori, Mattia; et al.
Graphical abstract: Highlights: Dynamics and control of reactive distillation using an extraneous entrainer for the production of n-butyl acetate are studied. Different multiplicities are found to appear depending on whether the azeotrope that forms with water is binary or ternary. Different control schemes depending on the type of azeotrope are proposed. Abstract: Several natural products have been suggested as effective agents for the treatment of cancer. Given the important role of CSCs (Cancer Stem Cells) in cancer, which is a trendy hypothesis, it is worth investigating the effects of pristimerin on CSCs as well as on the other malignant cells (MCF-7 and MDA-MB-231) of breast cancer. The anti-growth activity of pristimerin against MCF-7 and MCF-7s (cancer stem cell enriched population) cells was investigated by real time viability monitorization (xCELLigence System ® ) and ATP assay, respectively. Mode of cell death was evaluated using electron and fluorescence microscopies, western blotting (autophagy, apoptosis and ER-stress related markers) and flow cytometry (annexin-V staining, caspase 3/7 activity, BCL-2 and PI3K expressions). Pristimerin showed an anti-growth effect on cancer cells and cancer stem cells with IC50 values ranging at 0.38–1.75 μM. It inhibited sphere formation at relatively lower doses (<1.56 μM). Apoptosis was induced in MCF-7 and MCF-7s cells. In addition, extensive cytoplasmic vacuolation was observed, implying an incompleted autophagy as evidenced by the increase of autophagy-related proteins (p62 and LC3-II) with an unfolded protein response (UPR). Pristimerin inhibited the growth of MCF-7 and MDA-MB-231-originated xenografts in NOD.CB17-Prkdc scid /J mice. In mice, apoptosis was further confirmed by cleavage of PARP, activation of caspase 3 and/or 7 and TUNEL staining. Taken together, pristimerin shows cytotoxic activity on breast cancer both in vitro and in vivo . It seems to represent a robust promising agent for the treatment of breast cancer. Pristimerin's itself or synthetic novel derivatives should be taken into consideration for novel potent anticancer agent(s).